Evaluation of saw damage using diamond-coated wire in crystalline silicon solar cells by photoluminescence imaging. (11th April 2018) - Kinoshita, Kosuke; Kojima, Takuto; Suzuki, Ryota; Kawatsu, Tomoyuki; Nakamura, Kyotaro; Ohshita, Yoshio; Ogura, Atsushi
Abstract: Si ingots were sliced using a diamond-coated wire, and saw damage was observed even after damage removal etching and texturization. Since invisible microscopic damage was observed only under uncontrolled slice conditions, such damage was identified as saw damage. The wafers with saw damage exhibited the degradation of solar cell conversion efficiency (approximately 1–2% absolute). The results of external quantum efficiency (EQE) measurements showed a slight deterioration of EQE in the short wavelength region. Current–voltage characteristic measurements showed similar results that agreed with the EQE measurement results. In addition, EQE mapping measurements were carried out at various irradiation wavelengths between 350 and 1150 nm. Areas with dark contrasts in EQE mapping correspond to saw damage. In the cells with a low conversion efficiency, both EQE mapping and PL images exhibited dark areas and lines. On the other hand, in the cells with a high conversion efficiency, a uniform distribution of saw damage was observed even with the saw damage in the PL images. We believe that sophisticated control to suppress saw damage during sawing is required to realize higher conversion efficiency solar cells in the future.